Thoracic endovascular aortic repair in penetrating aortic ulcer combined with isolated left vertebral artery: A case report. Issue 37 (September 2019) - Fan, Weijian; Li, Chuanyong; Zheng, Guangfeng; Pan, Zhichang; Rong, Jianjie
Abstract: Rationale: Penetrating aorta ulcer (PAU) with isolated left vertebral artery (ILVA) is a rare condition, accounting for no more than 1% of all kinds of aorta diseases. And traditional treatment was open surgery with total arch replacement by elephant trunk. Here, we report a case of PAU combined with ILVA managed by thoracic endovascular aortic repair (TEVAR) technique. Patient concerns: A 65-year-old male with chronic hypertension and Nicotine abuse underwent intermittent back pain for 2 years and aggravated a bit for 1 week. Diagnoses: Preoperative computed tomography angiogram (CTA) indicated PAU combined with ILVA. Interventions: TEVAR was performed for PAU following with retrograde in situ fenestration and chimney technique for revascularization of ILVA and left subclavian artery (LSA), respectively. Outcomes: The operation was successfully and the patient was discharged from hospital after 1 week of treatment. Postoperatively, the images of CTA illustrated the patency of aorta, ILVA, and LSA without obvious endoleak. Besides, no ischemia attack or other relative syndromes were detected at 6-months follow-up. Lessons: This case demonstrates that TEVAR is an alternative to elephant trunk especially for PAU with ILVA. And it also showed the precise exposure of ILVA and necessity to reconstruct ILVA during TEVAR operation in order to reduce the occurrence of ischemia attack.